,Hutelle’: Auswirkungen einer tropischen Depression mit Starkniederschlägen auf den Ostabhang Madagaskars - Brand, Jürg (ERDKUNDE, 1995)
From March 1-3, 1993, the eastern escarpment of Madagascar was touched by the tropical depression ’Hutelle’, which, with its 440 mm rainfall within 24 hours, represented an event which occurs once every 50-100 years. Monitored catchments under mainly natural forest, secondary vegetation and shifting cultivation showed runoff coefficients of 61%, 73% and 79%, respectively. With soil water saturation numerous landslides occurred with local volumes of up to 192 m3/ha. Aside from factors of slope, exposure, and geology, the main cause of destabilization lies in higher infiltration capacity than lateral drainage capacity in the topsoil. Severe soil erosion occurred only on the small slash-and-burn plots, whereas on plots of upland rice 50-65 t/ha and on ginger plots 100-250 t/ha of soil loss were estimated. Damages for Malagasy farmers consist primarily in short-term harvest losses. According to the traditional shifting land-use system, damaged agricultural plots can be left to fallow, and soil fertility on sites suffering from landslides should be naturally regenerated within 10-20 years. Consequently, proposed permanent land-use within development activities must include an integrated drainage system in order to resist the devasting consequences of such major rainfall events.